Sand Fly–Associated Phlebovirus with Evidence of Neutralizing Antibodies in Humans, Kenya - David P. Tchouassi; Marco Marklewitz; Edith Chepkorir; Florian Zirkel; Sheila B. Agha; Caroline C. Tigoi; Edith Koskei; Christian Drosten; Christian Borgemeister; Baldwyn Torto; Sandra Junglen; Rosemary Sang (Emerging Infectious Diseases, 2019)
We describe a novel virus, designated Ntepes virus (NPV), isolated from sand flies in Kenya. NPV has the characteristic phlebovirus trisegmented genome architecture and is related to, but distinct from, Gabek Forest phlebovirus. Diverse cell cultures derived from wildlife, livestock, and humans were susceptible to NPV, with pronounced permissiveness in swine and rodent cells. NPV infection of newborn mice caused rapid and fatal illness. Permissiveness for NPV replication in sand fly cells, but not mosquito cells, suggests a vector-specific adaptation. Specific neutralizing antibodies were found in 13.9% (26/187) of human serum samples taken at the site of isolation of NPV as well as a disparate site in northeastern Kenya, suggesting a wide distribution. We identify a novel human-infecting arbovirus and highlight the importance of rural areas in tropical Africa for arbovirus surveillance as well as extending arbovirus surveillance to include hematophagous arthropods other than mosquitoes.